Enhancing mental health literacy and care through community-driven solutions in rural Bangladesh - Afreen, Ryan; Surya, Sanjna L.; Jara, Tasnim; Islam, Ima; Parvin, Rahana; Ferdousuzzaman, S. M.; Salah Uddin, Masum; Ahmed, Nahreen (Frontiers in Global Women's Health, 2024)
Women in rural Bangladesh encounter significant barriers to seeking mental healthcare, primarily due to stigmatization rooted in a lack of knowledge about mental health. To address this issue, community-based participatory research (CBPR) has been identified as a promising approach. CBPR involves the active collaboration of community members and stakeholders in the research process to tackle pressing community issues. This study examines the application of CBPR to enhance mental health awareness and education among women. The program described in this study leverages local technology centers and community health workers to boost participation in improving access to equitable mental healthcare and increasing health literacy. Implemented across three rural districts in Bangladesh, the program began with a needs assessment survey to evaluate participants' knowledge, experiences, and stigmatization of psychological conditions such as depression, anxiety, psychosis, suicide, and postpartum depression. This survey assessed baseline knowledge, personal experiences, and the perceived impact of mental wellness as a community issue. Additionally, five focus group discussions were conducted at local tech hubs with trained community health workers to explore participants' perceptions and attitudes toward mental health. These discussions highlighted the role of medical misinformation, the shortage of professionals, and other factors contributing to mental health stigmatization. The study's second phase would focus on developing digital medical content for screening at tech hubs, followed by live Q&A sessions with Bangladeshi health experts. This initiative aims to familiarize women with user-friendly telehealth services, fostering healthcare literacy and improving well-being in rural Bangladesh.